International night featuring cultures and traditions of various countries - UMP, PNC
More than 500 Universiti Malaysia Pahang (UMP) denizens turned up to liven up the International Night 2012 organised by the International Office together with the university's 1UMP1World Association Astana Hall, UMP on December 17, 2012.